Service-Learning: Recentering the Deaf Community in Interpreter Education - Shaw, Sherry; Roberson, Len (American annals of the deaf (Washington, D.C. 1886), 2009)
THE CONCEPT of recentering the Deaf community in interpreter education stems from the recent discussion of program evolution away from stakeholders and into academia highlighted by Monikowski and Peterson (2005). The University of North Florida, in the initial stages of developing a B.S. degree and M. Ed. concentration in ASL/English Interpreting, responded by developing stand-alone courses in service-learning, with hopes of prioritizing the needs of the Deaf community in curriculum development. The program was implemented in fall 2007, and the first cohort of students completed its second course in service-learning in fall 2008. Elements of the new program that indicate its progress toward recentering include an overview of service-learning as pedagogy in action, the distinction of service-learning from practicum and internship, implementation of the new courses, and the merging of the program’s strategic plan with the university’s commitment to community-based transformational learning.